PENGARUH TINGKAT PENGUNGKAPAN SUKARELA DAN BETA PASAR TERHADAP COST OF EQUITY CAPITAL (Studi Empiris Pada Perusahaan Manufaktur yang Terdaftar di BEI) - Eka Wulandari; Anik Malikah; Muhammad Cholid Mawardi (Universitas Islam Malang, 2017)
ABSTRACTThis study was conducted with the aim of: 1) to determine the effect of the VoluntaryDisclosure and Market Beta simultaneosly on the cost of equity capital, 2) to determine theeffect of the Voluntary Disclosure and Market Beta rate partially to the cost of equity capital.The population used in this study are all manufacturing companies listed on theIndonesian Stock Exchange (IDX) in 2012-2015. Sample selection using purposive sampling.Based on the criteria, obtained 77 companies that became the sample in this study. Themethod used in this research is doubled linier regression method.Based on the results of the analysis can be put forward several conclusions asfollows: 1) F test result indicate that the variable level of voluntary disclosure and marketbeta simultaneously significant effect on cost of equity capital. 2) t test result indicate that forthe variable disclosure rate voluntarily partially does not affect the cost of equity capital. 3)the market beta variable partially has a significant effect on the cost of equity capital.Keywords: Cost Of Equity Capital, Voluntary Diclosure, Market Beta